A grafted polyaryletherketone and its preparation method and application

Through the preparation method of grafted polyaryletherketone, the problem of poor combination of antibacterial agent and material structure is solved, efficient antibacterial and biocompatibility is achieved, and a controlled pore size structure is formed, which reduces the amount of antibacterial agent used and avoids Drug resistance and toxic side effects are improved, and the biocompatibility and antibacterial properties of the material are improved.

CN116120624BActive Publication Date: 2025-01-03CHANGCHUN HUAWOQI MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211499479.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-01-03
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

The combination of antibacterial agents and material structure in existing bone repair materials is poor, making it difficult to achieve efficient integration, and is costly and difficult to produce in large quantities, which easily leads to drug resistance and toxic side effects, and is difficult to simultaneously improve biocompatibility and antibacterial properties.

Method used

The preparation method of grafted polyaryletherketone is adopted, and the porous structure is formed by mixing biphenyl polyetherketoneketone imine and polyvinylpyrrolidone, ultrasonic dispersion and acidification heat treatment, and the connection of SBMA-Amino Compound-Ca Branch polymerization to obtain materials with controlled pore size and environmentally responsive antibacterial properties.

Benefits of technology

It achieves good biocompatibility and antibacterial effects in the bacterial growth environment, avoids drug resistance, reduces the amount of antibacterial agent added, reduces the damage to osteoblasts, and improves the biocompatibility and antibacterial properties of the material. , the formation of a controllable large-size pore structure is conducive to cell growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116120624B_ABST
    Figure CN116120624B_ABST
Patent Text Reader

Abstract

The present invention provides a grafted polyaryletherketone and a preparation method and application thereof. The preparation method of the grafted polyaryletherketone comprises: first preparing a soluble biphenyl-type polyetheretherketoneketoneimine, then obtaining a biphenyl-type polyetheretherketoneketone with a through-hole structure by phase conversion and acidification, and grafting a synthesized amino acid calcium salt to the biphenyl-type polyetheretherketoneketone under ultraviolet radiation to obtain a grafted polyaryletherketone. The grafted polyaryletherketone can be used as an antibacterial bone repair material, which has the following advantages: it has controllable large-size pores, which is conducive to better cell adhesion and growth; compared with existing antibacterial polymers, the present invention significantly reduces the amount of antibacterial agent added, but achieves more than or equal to the antibacterial agent polymer disclosed in the prior art; it saves costs, has no toxic side effects, has good biocompatibility, does not produce coating peeling, has stable performance, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a grafted polyaryletherketone and a preparation method and application thereof. Background Art

[0002] Bone repair materials usually refer to materials that are surgically implanted into the human body to repair bone defects and are biomedical materials. With the increase in bone defect cases, higher requirements are placed on bone repair materials, and bone repair materials have become a popular research topic in the field of biomedical materials. Compared with biomaterials with a single component or structure, the performance of composite biomaterials is adjustable. By selecting appropriate composite components or structures and adjusting the ratio between the components by physical blending or chemical methods, new materials with adjustable biocompatibility and mechanical properties can be obtained, which are suitable for practical medical applications such as antibacterial properties. However, for the polyaryletherketone implant materials required for biological orthopedics, the problems existing in the prior art are: first, due to the different structures of the antimicrobial agents and materials, moxifloxacin, gentamicin and vancomycin have poor binding and are difficult to integrate efficiently. In addition, other antimicrobial peptides are expensive and difficult to produce in large quantities. Moreover, the above antimicrobial agents are difficult to meet the processing requirements of polyaryletherketone, so a large amount of antimicrobial agents need to be added, which is not only prone to drug resistance, but also causes damage to osteoblasts; second, when preparing polyaryletherketone porous materials, pore-forming agents need to be added, and the pore-forming agents after pore formation are not easy to be removed from the materials, and the residual pore-forming agents will increase the toxic and side effects of the materials; third, when concentrated sulfuric acid and concentrated nitric acid are used for acid etching to form pores, small-sized pores less than 10 μm are usually formed on the surface of the material, and there will be no large-sized pores greater than 100 μm, which is not conducive to the growth of bone tissue and blood vessels; fourth, it is difficult for the prior art to simultaneously achieve the improvement of the biocompatibility of the composite, the reduction of toxic and side effects, and the improvement of antibacterial properties. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a grafted polyaryletherketone, and its preparation method comprises the following steps:

[0004] (1) Preparation of biphenyl type polyetheretherketoneketimine, the specific steps are as follows:

[0005] Aniline and 1,4-di(4-fluorobenzoyl)benzene were mixed, chloroform was added to dissolve, and then AlCl3 and Et3N were used as catalysts to react at room temperature to obtain N,N'-[1,4-phenylenebis[(4-fluorophenyl)methylene]]bis[benzylamine]

[0006] (DFK), according to the molar ratio of 1,4-di(4-fluorobenzoyl)benzene:aniline:AlCl3:Et3N of 1:3.2:3.4:10.2, DFK and biphenyl diphenol are mixed, cyclopentane is added to dissolve, and then a catalyst potassium carbonate is added, and a yellow solid is obtained after reaction at 135-140°C, and then the solid is crushed by a ball mill and washed with acetone and water for 3-5 times respectively, and then filtered and vacuum dried at 80-100°C for 12h to obtain a soluble biphenyl type polyetheretherketoneketimine, according to the molar ratio of DFK:biphenyl diphenol:potassium carbonate of 1:1:1.2-1:1:1.5;

[0007] (2) Preparation of porous biphenyl polyetheretherketoneketone, the specific steps are as follows:

[0008] The biphenyl type polyetheretherketoneketoneimine obtained in step (1) is mixed with polyvinylpyrrolidone, and then N-methylpyrrolidone is added to dissolve. After ultrasonic dispersion for 30-100 minutes, it is completely dissolved by heating and stirring, and then ultrasonic treatment for 30-100 minutes to obtain a casting solution. After degassing, the casting solution is placed in a deionized water coagulation bath at 20-30°C, and allowed to stand at room temperature for 24-48 hours. After repeating the coagulation bath and room temperature treatment for 3-7 times, a porous biphenyl type polyetheretherketoneketoneimine with through holes is obtained, and then an acidification heat treatment is performed at 140-150°C for 24-100 hours to obtain a porous biphenyl type polyetheretherketoneketone (PEBEKK); according to the mass ratio: the mass ratio of biphenyl type polyetheretherketoneketoneimine to polyvinylpyrrolidone is 1:10-1:5; the structure of the biphenyl type polyetheretherketoneketone is as follows:

[0009]

[0010] The n is a positive integer between 60 and 120;

[0011] (3) Preparation of surface coating monomer SBMA-Amino Compound-Ca, the preparation steps are as follows:

[0012] (a) Under nitrogen conditions, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA) is dissolved in a mixed solvent of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) in a volume ratio of 10:1-20:1 at 0-5°C, and a chlorination agent is added under stirring, according to the molar ratio of SBMA: chlorination agent is 1:3-1:1, and then stirred at 0-5°C for 1-1.5 hours, and then reacted at 35-40°C for 4-5 hours to obtain a mixed solution, and then the mixed solution is poured into ice water, and then a lithium bis(trifluoromethylsulfone)imide (LiNTf2) aqueous solution is added, wherein the molar ratio of LiNTf2 to SBMA is 1:1-3:1, and then extracted with dichloromethane, washed with water, filtered, and vacuum dried to obtain product 1 (SBMA-Cl-LiNTf2), wherein the chlorination agent is SOCl2 or POCl3, and the structural formula of the product 1 is as follows;

[0013]

[0014] (b) adding a mixed solution of tetrahydrofuran and triethylamine in a volume ratio of 10:1-20:1 to the amino compound, then adding a tetrahydrofuran solution of the product 1 (SBMA-Cl-LiNTf2) in step (a), reacting at 0-5°C for 1-1.5h, and then stirring at room temperature for 4-6h to obtain a discharge, and then dissolving the discharge in tetrahydrofuran under nitrogen protection and cooling to 0-1°C, and then adding a tetrahydrofuran solution of LiH, wherein the molar ratio of SBMA-Cl-LiNTf2:amino compound:LiH is 1:1:2-1:3:2; then stirring for 10-60min, heating to room temperature, and then stirring for 1-10h, filtering, acid washing, separation, rotary evaporation and vacuum drying to obtain product 2 (SBMA-Amino Compound); the amino compound is lysine or glycine;

[0015] (c) mixing the product 2 obtained in step (b) with calcium chloride, wherein the molar ratio of the product 2 to calcium chloride is 1:5-1:3, adding an acid solution so that the pH value of the solution is 7.0-8.5, reacting at 35-40° C. for 20-80 min, and then subjecting the mixture to rotary evaporation at 40-50° C., washing with an ethanol solution, and vacuum drying to obtain the product 3 (SBMA-Amino Compound-Ca); the acid solution is hydrochloric acid or sulfuric acid;

[0016] (4) PEBEKK-PSBMA-Amino Compound-Ca Graft Polymer

[0017] The porous PEBEKK obtained in step (2) is mixed with the aqueous solution of SBMA-Amino Compound-Ca obtained in step (3), wherein the molar ratio of PEBEKK to SBMA-Amino Compound-Ca is 1:1-30:1, and the mixture is irradiated with ultraviolet light for 90-120 minutes at 60-80°C under nitrogen protection, wherein the ultraviolet light intensity is 150-400 mW / cm 2 , and then washed with pure water, ethanol, and acetone solutions and vacuum dried to obtain a grafted polyaryletherketone, denoted as PEBEKK-PSBMA-Amino Compound-Ca grafted polymer, wherein the grafting amount is ~1-5 mg / g PEBEKK.

[0018] Furthermore, the grafting amount of the PEBEKK-PSBMA-Amino Compound-Ca grafted polymer in step (4) is 2-3 mg / g PEBEKK.

[0019] The present invention also provides an application of the grafted polyaryletherketone in the field of osteogenic biomaterials.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] Compared with the prior art, even in a bacterial growth environment (PH < 7), the material obtained by the present invention has good biocompatibility and no toxic side effects. It can not only achieve effective antibacterial and calcium ion release, but also form controllable large-size pores with a pore size of ≥100 μm, wherein the controllable porous structure will be beneficial to the movement of cells, the transportation of nutrients and the discharge of metabolites, which is beneficial to the growth of cells or tissues, thereby enabling cells to achieve better adhesion and growth, and can improve the biologically inert surface of the material, improve biocompatibility, and be beneficial to osteogenesis; in addition, the material obtained by the present invention can prevent bacteria, proteins and other pollutants from adhering to the surface, thereby avoiding the reduction or even disappearance of the antibacterial effect of the material surface; the material obtained by the present invention can achieve environmental responsiveness, in the slightly acidic environment generated after bacterial infection In the weakly acidic environment of bacterial infection, it can release calcium ions to the maximum extent to promote osteogenesis; in the acidic environment produced by bacteria, in the in vitro experiment of the material obtained by the present invention, the grafting mass of 1-5 mg / g PEBEKK can achieve an antibacterial rate of 96-99%, and the effect reaches the standard antibacterial agent disclosed in the prior art when the amount of antibacterial agent added is much smaller than that of the existing antibacterial agent. Compared with the material with added antibacterial agent, the material obtained by the present invention reduces the addition of antibacterial agent, does not cause damage to osteoblasts, and saves costs; the grafted polyaryletherketone obtained by the present invention does not produce coating peeling, and has stable physical and chemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The H NMR spectrum of the product 2 obtained in step 3 of Example 1 1 H-NMR spectrum;

[0023] Figure 2 a, b, and c are infrared spectra comparison diagrams of PEBEKK in step 2 of Example 1, monomer SBMA-LYS-Ca in step 3, and PEBEKK-PSBMA-LYS-Ca in step 4, respectively;

[0024] Figure 3 This is a comparison chart of alkaline phosphatase (ALP) activity data of PEBEKK in step 2 and PEBEKK-PSBMA-LYS-Ca in step 4 of Example 1;

[0025] Figure 4 These are comparison photos of the control group (Control), PEBEKK in step 2 of Example 1, and PEBEKK-PSBMA-LYS-Ca in step 4 after acting with Escherichia coli and Staphylococcus aureus for 7 days, respectively. DETAILED DESCRIPTION

[0026] Embodiment 1:

[0027] Step 1: Preparation of biphenyl-type polyetheretherketoneketimine

[0028] Aniline and 1,4-di(4-fluorobenzoyl)benzene were mixed, chloroform was added to dissolve, and AlCl3 and Et3N were used as catalysts to react at room temperature to obtain N,N'-[1,4-phenylenebis[(4-fluorophenyl)methylene]]bis[benzylamine] (DFK), calculated according to the molar ratio: 1,4-di(4-fluorobenzoyl)benzene:aniline:AlCl3:Et3N=1:3.2:3.4:10.2; DFK was mixed with biphenyldiphenol, cyclopentane was added to dissolve, and then potassium carbonate was added as a catalyst, and a yellow solid was obtained after reaction at 140°C, which was then crushed with a ball mill and washed with acetone and water for 3 times respectively, and then filtered and vacuum dried at 80°C for 12 hours to obtain a soluble biphenyl-type polyetheretherketoneketimine, according to the molar ratio: DFK:biphenyldiphenol:potassium carbonate is 1:1:1.2;

[0029] Step 2: Preparation of porous biphenyl-based polyetheretherketoneketone

[0030] The obtained biphenyl type polyetheretherketoneketoneimine was mixed with polyvinylpyrrolidone by a phase inversion method, and then N-methylpyrrolidone was added to dissolve. After ultrasonic dispersion for 30 minutes, the mixture was heated to dissolve, and then ultrasonicated for 30 minutes to obtain a casting solution. After degassing, the casting solution was poured onto a glass plate covered with silica gel, and placed in the air for 30 seconds. The glass plate was quickly placed in a deionized water coagulation bath at room temperature, and allowed to stand at room temperature for 24 hours. A porous biphenyl type polyetheretherketoneketoneimine with through holes was obtained by repeatedly changing the coagulation bath 3 times and placing at room temperature. After acidification heat treatment at 140°C for 24 hours, a porous biphenyl type polyetheretherketoneketone PEBEKK was obtained. The structural formula of the PEBEKK is as follows:

[0031]

[0032] Wherein n is a positive integer and is 60-120; the porous biphenyl type polyetheretherketoneketone has a pore size of 100-300 μm, the pore wall is composed of small holes of 1-5 μm, and it has a porous structure that runs through from top to bottom.

[0033] Step 3: Preparation of surface coating monomer SBMA-LYS-Ca, the preparation steps are as follows:

[0034] (a) In nitrogen, dry [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide SBMA was dissolved in a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) at 0-5°C, with a solvent volume ratio of 17:1, and SOCl2 was added under stirring, with a molar ratio of SBMA:SOCl2 of 1:2. After stirring for 1 hour, the mixture was reacted at 35°C for 5 hours to obtain a mixed solution, which was then poured into ice water, and an aqueous solution of lithium bis(trifluoromethylsulfone)imide (LiNTf2) was added, wherein the molar ratio of LiNTf2 to SBMA was 1:1. The product 1 (SBMA-Cl-LiNTf2) was obtained after extraction with dichloromethane, washing with water, suction filtration, and vacuum drying.

[0035] (b) adding a mixed solution of tetrahydrofuran and triethylamine in a volume ratio of 15:1 to lysine (LYS), and then mixing it with the tetrahydrofuran solution of product 1 in step (a), reacting at 0°C for 1h, and then stirring at room temperature for 4h to obtain a discharge, dissolving the discharge in tetrahydrofuran under nitrogen protection and cooling to 0-1°C, and then adding LiH tetrahydrofuran solution, wherein the molar ratio of SBMA-Cl-LiNTf2:LYS:LiH is 1:1:2; then stirring for 30min, heating to room temperature, and then stirring at room temperature for 2h, filtering, acid washing, separation, rotary evaporation and vacuum drying to obtain product 2 (SBMA-LYS);

[0036] (c) mixing the product 2 obtained in step (b) with calcium chloride, wherein the molar ratio of the product 2 to calcium chloride is 1:5, adding hydrochloric acid solution so that the pH of the solution is adjusted to 8.0, reacting at 35° C. for 30 min, then rotary evaporating at 40° C., washing with ethanol solution, and vacuum drying to obtain product 3 (SBMA-LYS-Ca), and the reaction process of steps (a) to (c) is as follows;

[0037]

[0038] Product 3 (SBMA-LYS-Ca) 1 H-NMR diagram is shown in Figure 1 ,Depend on Figure 1 It can be seen that product 3 was successfully obtained in this example.

[0039] Step 4: PEBEKK-PSBMA-LYS-Ca grafted polymer, preparation steps are as follows:

[0040] The porous PEBEKK obtained in step 2 was mixed with the aqueous solution of SBMA-LYS-Ca obtained in step 3, the molar ratio of PEBEKK to SBMA-LYS-Ca being 10:1, and the mixture was irradiated with ultraviolet light for 120 min at 60°C under nitrogen protection, wherein the ultraviolet light intensity was 250 mW / cm 2 , PEBEKK-PSBMA-LYS-Ca grafted polymer was obtained after washing with pure water, ethanol, and acetone solutions and vacuum drying, with a grafting mass of 2-3 mg / g PEBEKK.

[0041] The infrared spectra of PEBEKK, monomer SBMA-LYS-Ca and grafted polymer of Example 1 are shown in Figure 2 :Functional group 3417cm -1 (v-OH), 3150cm -1 (vC=C), 1346cm -1 (vS=O2),1190cm -1 (vC-N),1179cm -1 (vC-F),1054cm -1 (vC-F),956cm -1 The formation of (vC=C) proves the successful synthesis of monomer SBMA-LYS-Ca. 3150cm -1 (vC=C),956cm -1 The disappearance of (vC=C) confirmed the successful grafting of the polymer.

[0042] Example 2

[0043] The cytotoxicity of the porous biphenyl polyetheretherketoneketone PEBEKK of step 2 of example 1 and the grafted polymer PEBEKK-PSBMA-LYS-Ca of step 4 before and after surface grafting was tested.

[0044] For the cytotoxicity experiment, two samples were sterilized and placed in 48-well plates. MC3T3-E1 cells were cultured at 5 × 10 4 Cells were inoculated on the sample surface at a density of 100 cells / well and cultured in a cell culture incubator for 24 hours. After the culture was completed, the 48-well plate was removed and the culture medium was removed. After adding 100 μl of live and dead cell staining reagent to each well and staining at room temperature for 30 minutes, the cell survival rate of polymer PEBEKK was 99% (p<0.01) and the cell survival rate of grafted polymer PEBEKK-PSBMA-LYS-Ca was 99% (p<0.01). In summary, this shows that polymer PEBEKK and PEBEKK-PSBMA-LYS-Ca are non-biotoxic.

[0045] Example 3

[0046] Cell proliferation assay

[0047] The grafted polymer PEBEKK-PSBMA-LYS-Ca of step 4 of test example 1 was sterilized and a 1×10 4 cell / mL of MC3T3-E1 cell suspension was cultured for 1, 3, and 5 days, then a culture medium containing 10% CCK-8 was added, and the absorbance of each well was measured at a wavelength of 450nm using a microplate reader. It was found that the absorbance of PEBEKK-PSBMA-LYS-Ca was 0.5 on the first day, 1.0 on the third day, and 2.0 on the fifth day. The increase in the absorbance value proved the proliferation of the number of MC3T3-E1 osteoblasts, thereby indicating that the PEBEKK-PSBMA-LYS-Ca obtained by the present invention has a good ability to promote cell proliferation.

[0048] Example 4

[0049] In vitro osteogenic activity verification

[0050] The porous biphenyl polyetheretherketoneketone PEBEKK of step 2 of test example 1 and the graft polymer PEBEKK-PSBMA-LYS-Ca of step 4 were added with a density of 3×10 3 Cells were cultured for 4 and 7 days, and then 100 μl of RIPA lysis buffer was added to fully lyse the cells. The cell lysate was collected and the supernatant was collected by centrifugation for 5 min. The protein concentration of the sample was tested by alkaline phosphatase (ALP). The ALP activity per unit protein concentration of the sample was calculated based on the ALP activity and protein concentration. Figure 3 The horizontal axis is the cell culture time (days), and the vertical axis is the alkaline phosphatase (ALP) activity; Figure 3 The grafted polymer PEBEKK-PSBMA-LYS-Ca in step 4 is beneficial to the differentiation of bone marrow mesenchymal stem cells into osteoblasts. The ALP value is 1.25mmol / min / mg on the 4th day and 1.68mmol / min / mg on the 7th day, and it increases significantly over time, showing the highest growth rate of ALP value. Although the porous biphenyl polyetheretherketoneketone PEBEKK has osteogenic activity, its activity is not as good as that of PEBEKK-PSBMA-LYS-Ca material. Figure 3 It can be concluded that PEBEKK-PSBMA-LYS-Ca has better osteogenic activity.

[0051] Example 5

[0052] Preparation of bacterial culture medium:

[0053] The agar medium was prepared as follows: 4 g LB agar (Qingdao Nissui) was weighed into 100 ml sterile water, sterilized under high pressure steam for 25 min, and poured into plates at about 60°C, 15-20 ml per plate.

[0054] The liquid culture medium was prepared by adding 1 g / 100 ml of tryptone, 0.5 g / 100 ml of yeast extract and 1 g / 100 ml of sodium chloride, adjusting the pH of the culture medium to 7.4 with NaOH, sterilizing the culture medium with steam under high pressure for 25 min, storing the culture medium in a refrigerator at 4°C and keeping the culture medium at 37°C for later use.

[0055] The components of PBS added to the control group (Control) are: Na + (140-150mM), K + (4-6mM),Mg 2+ (1-3mM), Ca 2+ (2-4mM),Cl - (140-150mM),HCO3 - (3-10mM),HPO4 - (0.5-1.0mM), SO4 2- (0.5-1.0mM), pH (7.0-7.5).

[0056] Flat coating method

[0057] The porous biphenyl polyetheretherketoneketone PEBEKK (marked as A) of step 2 of test example 1 and the graft polymer PEBEKK-PSBMA-LYS-Ca (marked as B) of step 4 were pretreated in a buffer solution PBS and an acidic buffer solution of pH = 4.6 for 24 hours, and then the materials were sterilized and placed in a 48-well plate, and the bacterial solution was diluted to 10 5 ~10 6 CFU / mL, the test bacteria were Staphylococcus aureus and Escherichia coli after culturing at 37℃ for 24h, the attached bacteria were eluted with PBS solution and ultrasound, and then 100μL of the 10-fold diluted bacterial solution was added to the agar medium and the changes were observed for 7 days. Figure 4It can be seen that after 7 days, the amount of bacteria in the control group increased, the amount of bacteria in group A decreased, but the antibacterial effect of group B was the best, which shows that the grafted polymer PEBEKK-PSBMA-LYS-Ca obtained in step 4 can maintain broad-spectrum antibacterial activity against Staphylococcus aureus and Escherichia coli after 7 days; through measurement, it is found that the antibacterial rate for the two bacteria can reach 98.5-99%, which shows that the PEBEKK-PSBMA-LYS-Ca material has good antibacterial properties against Staphylococcus aureus and Escherichia coli. Where s is Staphylococcus aureus and p is Escherichia coli.

[0058] Example 6

[0059] The preparation of the biphenyl type polyetheretherketoneketoneimine in step 1 and the preparation of the porous biphenyl type polyetheretherketoneketone in step 2 are consistent with those in Example 1;

[0060] Step 3 Preparation of surface coating monomer SBMA-GLY-Ca, the preparation steps are as follows:

[0061] (a) Dry [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide SBMA was dissolved in a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) at 0°C in nitrogen, with a solvent volume ratio of 17:1, and POCl3 was added under stirring, with a molar ratio of SBMA:POCl3 of 1:1. After stirring for 30 minutes, the mixture was reacted at 30°C for 3 hours to obtain a mixed solution, which was then poured into ice water, and an aqueous solution of lithium bis(trifluoromethylsulfone)imide (LiNTf2) was added, wherein the molar ratio of LiNTf2 to SBMA was 1:1. The product 1 (SBMA-Cl-LiNTf2) was obtained after extraction with dichloromethane, washing with water, suction filtration and vacuum drying.

[0062] (b) adding a mixed solution of tetrahydrofuran and triethylamine in a volume ratio of 15:1 to glycine (GLY), and then mixing it with the tetrahydrofuran solution of product 1 in step (a), reacting at 0°C for 1h, and then stirring at room temperature for 4h to obtain a discharge, dissolving the discharge in tetrahydrofuran under nitrogen protection and cooling to 0-1°C, and then adding LiH tetrahydrofuran solution, wherein the molar ratio of SBMA-Cl-LiNTf2:glycine:LiH is 1:1:2; then stirring for 30min, heating to room temperature, and then stirring at room temperature for 2h, filtering, acid washing, separation, rotary evaporation and vacuum drying to obtain product 2 (SBMA-GLY);

[0063] (c) mixing the product 2 obtained in step (b) with calcium chloride, wherein the molar ratio of the product 2 to calcium chloride is 1:5, adding an acid solution so that the pH of the solution is 8.0, reacting at 35° C. for 30 min, then rotary evaporating at 40° C., washing with an ethanol solution, and vacuum drying to obtain a product 3, which is recorded as SBMA-GLY-Ca;

[0064] The PEBEKK-PSBMA-GLY-Ca grafted polymer of step 4 is prepared as follows:

[0065] The porous PEBEKK obtained in step 2 was mixed with the aqueous solution of SBMA-GLY-Ca obtained in step 3, the molar ratio of PEBEKK to SBMA-GLY-Ca was 8:1, and the mixture was irradiated with ultraviolet light for 120 min at 60°C under nitrogen protection, wherein the ultraviolet light intensity was 250 mW / cm 2 , PEBEKK-PSBMA-GLY-Ca grafted polymer was obtained after washing with pure water, ethanol, and acetone solution and vacuum drying, and the grafting mass was 1-5 mg / g PEBEKK.

[0066] The PEBEKK-PSBMA-GLY-Ca graft polymer obtained in Example 6 has good cell proliferation, osteogenic properties, biocompatibility and non-toxicity, and its antibacterial rate can reach 96-98%.

[0067] In summary: It is currently difficult for osteogenic materials synthesized by the prior art to simultaneously achieve a pore structure suitable for cell growth, good cell proliferation, osteogenic performance, biocompatibility and non-toxicity; while the present invention reduces production costs, through the synergistic effect of raw materials, ratios and processes, so that the obtained grafted polymer can simultaneously achieve a pore structure suitable for cell growth and have good cell proliferation, osteogenic performance, biocompatibility and non-toxicity while reducing the amount of antibacterial components added, and the antibacterial rate can reach 96-99%.

Claims

1. A grafted polyaryletherketone, characterized in that: Its preparation method comprises the following steps: (1) Aniline and 1,4-di(4-fluorobenzoyl)benzene are mixed, chloroform is added to dissolve, and AlCl3 and Et3N are used as catalysts to react at room temperature to obtain N,N'-[1,4-phenylenebis[(4-fluorophenyl)methylene]]bis[benzylamine]DFK, according to the molar ratio of 1,4-di(4-fluorobenzoyl)benzene:aniline:AlCl3:Et3N of 1:3.2:3.4:10.2, DFK is mixed with biphenyldiphenol, cyclopentane is added to dissolve, and then potassium carbonate is added as a catalyst, and a yellow solid is obtained after reaction at 135-140°C, which is then crushed by a ball mill and washed with acetone and water for 3-5 times respectively, and then filtered and vacuum dried at 80-100°C for 12 hours to obtain a soluble biphenyl type polyetheretherketoneketimine, according to the molar ratio of DFK:biphenyldiphenol:potassium carbonate of 1:1:1.2-1:1:1.5; (2) The biphenyl type polyetheretherketoneketoneimine obtained in step (1) is mixed with polyvinylpyrrolidone, and then N-methylpyrrolidone is added to dissolve. After ultrasonic dispersion for 30-100 minutes, it is completely dissolved by heating and stirring, and then ultrasonic treatment for 30-100 minutes to obtain a casting solution. After degassing, the casting solution is placed in a deionized water coagulation bath at 20-30°C, and allowed to stand at room temperature for 24-48 hours. After repeating the coagulation bath and room temperature treatment for 3-7 times, a porous biphenyl type polyetheretherketoneketoneimine with through holes is obtained, and then an acidification heat treatment is performed at 140-150°C for 24-100 hours to obtain a porous biphenyl type polyetheretherketoneketone PEBEKK; according to the mass ratio: the mass ratio of biphenyl type polyetheretherketoneketoneimine to polyvinylpyrrolidone is 1:10-1:5; the structure of the PEBEKK is as follows: The n is a positive integer between 60 and 120; (3) The preparation steps of the surface coating monomer SBMA-Amino Compound-Ca are as follows: (a) Under nitrogen conditions, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide SBMA is dissolved in a mixed solvent of tetrahydrofuran (THF) and N,N-dimethylformamide DMF with a volume ratio of 10:1-20:1 at 0-5°C, and a chlorination agent is added under stirring, according to the molar ratio of SBMA: chlorination agent is 1:3-1:1, and then stirred at 0-5°C for 1-1.5h, and then reacted at 35-40°C for 4-5h to obtain a mixed solution, and then the mixed solution is poured into ice water, and then a lithium bis(trifluoromethylsulfone)imide LiNTf2 aqueous solution is added, wherein the molar ratio of LiNTf2 to SBMA is 1:1-3:1, and then extracted with dichloromethane, washed with water, filtered, and vacuum dried to obtain the product 1SBMA-Cl-LiNTf2, wherein the chlorination agent is SOCl2 or POCl3; (b) adding a mixed solution of tetrahydrofuran and triethylamine in a volume ratio of 10:1-20:1 to the amino compound, then adding the tetrahydrofuran solution of SBMA-Cl-LiNTf2 in step (a), reacting at 0-5°C for 1-1.5h, stirring at room temperature for 4-6 hours to obtain a discharge, dissolving the discharge in tetrahydrofuran under nitrogen protection and cooling to 0-1°C, and then adding a tetrahydrofuran solution of LiH, wherein the molar ratio of SBMA-Cl-LiNTf2:amino compound:LiH is 1:1:2-1:3:2; stirring for 10-60min, heating to room temperature, stirring for 1-10h, filtering, acid washing, separation, rotary evaporation and vacuum drying to obtain the product 2SBMA-Amino Compound; the amino compound is lysine or glycine; (c) mixing the product 2 obtained in step (b) with calcium chloride, wherein the molar ratio of the product 2 to calcium chloride is 1:5-1:3, adding an acid solution so that the pH value of the solution is 7.0-8.5, reacting at 35-40° C. for 20-80 min, and then subjecting the mixture to rotary evaporation at 40-50° C., washing with an ethanol solution, and vacuum drying to obtain the product 3SBMA-Amino Compound-Ca; the acid solution is hydrochloric acid or sulfuric acid; (4) PEBEKK-PSBMA-Amino Compound-Ca Graft Polymer The porous PEBEKK obtained in step (2) is mixed with the aqueous solution of SBMA-Amino Compound-Ca obtained in step (3), wherein the molar ratio of PEBEKK to SBMA-Amino Compound-Ca is 1:1-30:1, and the mixture is irradiated with ultraviolet light for 90-120 minutes at 60-80°C under nitrogen protection, wherein the ultraviolet light intensity is 150-400 mW / cm 2 , and then washed with pure water, ethanol, and acetone solutions and vacuum dried to obtain a grafted polyaryletherketone, denoted as PEBEKK-PSBMA-Amino Compound-Ca grafted polymer, wherein the grafting amount is ~1-5 mg / g PEBEKK.

2. A grafted polyaryletherketone according to claim 1, characterized in that: The grafting amount of the PEBEKK-PSBMA-Amino Compound-Ca grafted polymer in step (4) is 2-3 mg / g PEBEKK.

3. Use of the grafted polyaryletherketone according to claim 1 or 2 in the field of bone repair materials.